Effect of Disinfection on the Dimensional Stability of Polyether Impression Materials - Handan Yilmaz, DDS, PhD;1 Cemal Aydin, DDS, PhD;1 Basak Gul, DDS;2 (Journal of Prosthodontics, 2007)
Difficulties in sterilizing impressions have led to chemical disinfection solutions as an alternative; however, some impression materials are more sensitive to humidity. For example, polyether impression materials are more hydrophilic.